2018
DOI: 10.1097/corr.0000000000000531
|View full text |Cite
|
Sign up to set email alerts
|

Patients With Chronic Obstructive Pulmonary Disease Are at Higher Risk for Pneumonia, Septic Shock, and Blood Transfusions After Total Shoulder Arthroplasty

Abstract: Background Chronic obstructive pulmonary disease (COPD) has been associated with several complications after surgery, including pneumonia, myocardial infarction, septic shock, and mortality. To the authors' knowledge, there has been no work analyzing the impact of COPD on complications after total shoulder arthroplasty (TSA). Although previous work has elucidated the complications COPD has on TKA and THA, extrapolating the results of lower extremity arthroplasty to TSA may prove to be inaccurate. Compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 26 publications
(32 reference statements)
1
20
0
Order By: Relevance
“… 19 , 29 Diabetes has been shown to be an independent risk factor for wound complications, stroke, renal failure, and sepsis after SA. 18 , 31 Similarly, Lee et al 26 found COPD to be an independent risk factor for pneumonia and septic shock among patients undergoing TSA.…”
Section: Discussionmentioning
confidence: 93%
“… 19 , 29 Diabetes has been shown to be an independent risk factor for wound complications, stroke, renal failure, and sepsis after SA. 18 , 31 Similarly, Lee et al 26 found COPD to be an independent risk factor for pneumonia and septic shock among patients undergoing TSA.…”
Section: Discussionmentioning
confidence: 93%
“…For instance, Lee et al expressed that patients that underwent orthopedic surgeries and suffering from COPD develop severe complications as the need for blood transfusion, septic shock, and anemia which usually require postoperative ICU admission. 13 Klasan et al also supported those same findings in a patient-matched study of lower-limb orthopedics. 14 Friedman et al also reported that having benign heart murmurs was an independent significant factor for predicting ICU admissions after orthopedic surgeries.…”
Section: Predictors For Icu Admissions Following Orthopedic Surgeriesmentioning
confidence: 65%
“…The first independent risk factor of postcholecystectomy pneumonia was preoperative chronic obstructive pulmonary disease, which is the most significant predictor in our study. Several studies have examined the association between chronic obstructive pulmonary disease and postoperative pneumonia [ 13 , 15 , 16 ]. Results about whether chronic obstructive pulmonary disease is correlated with postoperative pulmonary complications are controversial.…”
Section: Discussionmentioning
confidence: 99%